Analisis Kebutuhan Lembar Kerja Mahasiswa Elektronik Berbasis Case Method pada Mata Kuliah Evaluasi Proses dan Hasil Belajar - Natalia, Desfaur; Wicaksana, Ervan Johan (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2023)
The purpose of this study was to find out the needs of students for Electronic Media Student Worksheets (E-LKM) Based on Case Studies in Process Evaluation and Learning Outcome Courses. This research method uses descriptive qualitative. Data collection techniques in this study were interview and questionnaire techniques. Data analysis using data reduction, data presentation and conclusion. The research subjects were lecturers in the process and learning outcomes evaluation course, and 3rd semester students who took the process and learning outcomes evaluation course. Based on the survey data in the form of the results of filling out the questionnaire, 53.7% of students did not have reference books related to the process evaluation and learning outcomes evaluation course. Most lecturers use PPT to deliver material. Assignments are given in the form of projects and in the form of case studies. Based on the questionnaires, 80.5% of students liked learning with case studies. They argue that case study learning makes them challenged to solve cases and improve critical thinking skills. 95.1% of students gave a response that agreed if the process evaluation and learning outcomes course contained electronic worksheets. Therefore, it is necessary to develop case study-based electronic student worksheets (E-LKM) to help and facilitate students in understanding material concepts and doing assignments given by lecturers.